Teaching Online Social Skills to Students With Emotional and Behavioral Disorders. Issue 2 (June 2016) - Morgan, Joseph John; Higgins, Kyle; Miller, Susan; Pierce, Thomas B.; Boone, Randall; Tandy, Richard
Students with emotional and behavioral disorders (EBDs) often lack appropriate social skills. Participation in direct and explicit instruction related to social skills is common in their educational programming. For these interventions to be effective, it is important that students have the opportunity to apply them in the natural environment. Increases in the use of technology have created new natural environments for social participation, with their own specific rules for social interaction. Although not specifically studied, it has been theorized that students with EBD will display social deficits in online environments. This study focused on teaching eight online social skills (OSS) to students with EBD. Two instructional conditions were compared: traditionally based OSS instruction (OSSI) involving paper-and-pencil and OSSI involving practice in an online social environment. Twenty-three culturally and linguistically diverse adolescent students with EBD (mean age of 13.35) participated in this intervention. Findings indicated that both interventions were effective at increasing students' identification of problem behaviors in an online environment and that students believed learning about OSS was important at the end of instruction. Based on overall knowledge acquisition scores, however, neither intervention produced significant results. Implications for the incorporation of this instruction into social skills interventions are discussed.